A Proposed Vision To Strengthen The Psychological And Social Support For Orphans In Care Homes - Deea Ahmed Alkurd (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
The study aimed to identify the necessity of building a proposed vision to enhance the psychological and social support of orphans in care homes, and the researcher reviews in this study the definition of the study terms represented in psychological and social support and orphanages and care homes, as well as the difficulties and challenges facing orphan care institutions in providing psychological and social support to orphans The researcher used the descriptive desktop approach to identify the literature related to developing the proposed vision to enhance psychological and social support for orphans in care homes. The study showed that providing psychological and social support helps orphans Depositors in care homes to face life stresses and positive adaptation to the circumstance of loss and overcome difficulties before them in order to develop their psychological and social compatibility, as well as enable them through programs to explore their capabilities and develop their capabilities and raise their competencies. The study recommended providing orphan care institutions with the amenities, entertainment and educational games aimed at contributing to creating a positive atmosphere aimed at achieving psychological and social compatibility for the orphans in which they are placed1. Ibrahim, Zakaria (1973 AD) The Artist and the Man, Egypt: Dar Gharib for Printing and Publishing.2. Istiti, Tasnim, Muhammad Jamal. Hassan (2007 CE): Orphan's Rights in Islamic Jurisprudence, Master Thesis, College of Graduate Studies, An-Najah National University, Nablus, Palestine.3. Al-Buraq, Amna (2011): The needs of adults of unknown parentage after leaving institutions for orphans, the first Saudi conference for orphan care.4. Jalal, Nusseibeh (2017): Psychological care for Syrian refugee orphans,